Domains Affected And Bookkeeping Records Incurred Due To Covid-19 Pandemic - Maria Moraru (Communications of International Proceedings, 2021)
The COVID-19 pandemic represents the greatest crisis of all as it not involves the lack of the financial resources, but the lack of the ability to protect the health of the human resource. Uncertainty has reached its highest level of all previous crises as            COVID-19 pandemic has striken all economy`s sectors, one by one, from health system to education, to transport and traveling. As an invisible threat, it rapidly infected countries worldwide and put a lot of pressure on the health sector, making it harder for all other companies to manage the human and material resources, so in order to keep the situation under control and going concern, events have to be recorded accordingly with the accounting principles and law framework. By this research we want to highlight the course taken by the romanian economy, starting from the macroeconomic perspective transposed as effects manifested on the labor market, sustained by the law framework and accounting practices given rise due to unforeseeable event such as the COVID-19 pandemic.
Keywords: Practices; Accounting; Unemployment; COVID-19